Strengthening Good Corporate Governance through Standardization of SOPs in Islamic Financial Institutions - Aini, Retno; Eko Arief Cahyono; Dwi Anjani; Ilaina Tazkiroh; Isna Nurfaizah; Aditya Jefri Ardiansyah; Abror Yusuf; Evan Maulana Jauhari; Sella Damawati (Li Falah: Journal of Islamic Economics and Business, 2026)
This study aims to analyze the role of Standard Operating Procedure (SOP) standardization in strengthening the implementation of Good Corporate Governance (GCG) within Islamic financial institutions by addressing the limited integration between operational procedures and governance principles identified in previous research. A qualitative library research approach was employed using secondary data collected from scientific journals, books, regulations, and other relevant literature, which were analyzed through content analysis and descriptive qualitative techniques. The findings indicate that SOP standardization plays a strategic role in supporting the principles of transparency, accountability, responsibility, independence, and fairness while serving as an instrument of internal control, risk management, and Sharia compliance to enhance organizational effectiveness, strengthen stakeholder trust, and promote sustainable governance practices. The novelty of this study lies in positioning SOP standardization as an implementation mechanism that translates GCG principles into concrete operational activities within Islamic financial institutions.